2021
DOI: 10.1016/j.devcel.2021.10.007
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetochore life histories reveal an Aurora-B-dependent error correction mechanism in anaphase

Abstract: Highlights d Chromosomes are at a considerable and continual risk of mis-segregation d Metaphase dynamics forecast lazy kinetochores and their correction in anaphase d Aurora B spindle midzone gradient enables phosphorylation of kinetochore substrates d Results suggest midzone originated Aurora B activity destabilizes erroneous attachments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…2A, B ). 3D kinetochore tracking 28 , and measurement of EGFP-HURP intensity along the associated K-fibre showed that as metaphase sister kinetochores oscillated back-and-forth, HURP was exclusively present on depolymerising K-fibres (associated to the leading kinetochore sister), and never on the growing K-fibre (associated to the trailing kinetochore sister) (Fig. 2C, D ).…”
Section: Resultsmentioning
confidence: 98%
“…2A, B ). 3D kinetochore tracking 28 , and measurement of EGFP-HURP intensity along the associated K-fibre showed that as metaphase sister kinetochores oscillated back-and-forth, HURP was exclusively present on depolymerising K-fibres (associated to the leading kinetochore sister), and never on the growing K-fibre (associated to the trailing kinetochore sister) (Fig. 2C, D ).…”
Section: Resultsmentioning
confidence: 98%
“…In a set of recent studies, it was reported that the Aurora B midzone gradient mediates phosphorylation of outer kinetochore proteins even during anaphase [201], at similar sites as in pre-anaphase cells [158]. Thus, it seems that error correction mediated by Aurora B has an additional layer operating in early anaphase [194,202] (Figure 7, route 2), which could explain previous observations that the proportion of lagging chromosomes during anaphase is by an order of magnitude higher than the proportion of cells with aneuploidy in the same population [203]. Furthermore, this led to a redefinition of lagging kinetochores by introducing a new term of 'lazy' kinetochores, transiently lagging kinetochores that are quickly and efficiently corrected during the early anaphase by the Aurora B-dependent mechanism [194] (Figure 7, route 2).…”
Section: Different Ways To Mis-segregation Through Polar Chromosomesmentioning
confidence: 99%
“…A recent study presented an intriguing model in which difficulties associated with the inability of unaligned chromosomes to congress are not necessarily caused by defects related to MTs, SAC, or motors but rather due to the presence of a complex system of organelle remnants behind the spindle poles, termed endomembranes, which could ensheat polar chromosomes and prevent their efficient capture by MTs, resulting in aneuploidy [189]. However, for definitive conclusions about the mechanisms underlying unaligned chromosome mis-segregation in unperturbed cells, one would need to track the origin and fate of mis-segregations through whole mitosis, similar to what was done recently from metaphase to telophase in human cells [194].…”
Section: Different Ways To Mis-segregation Through Polar Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the rate of lagging chromosomes in human cells was estimated at 5%; however, imaging limitations and data relying on fixed samples provide an incomplete picture. Using lattice light-sheet imaging and computational analysis of 3D kinetochore trajectory tracking, Andrew McAinsh, Nigel Borroughs and colleagues 1 propose that the risk of mis-segregation in human mitotic cells is higher than previously assumed. They quantify metaphase sister chromatid behaviour as a predictor for lagging chromosomes in anaphase and collect evidence for the existence of an early anaphase correction mechanism orchestrated by the kinase Aurora B.…”
mentioning
confidence: 99%